Length-weight relationship and relative condition factor of five Labeo spp. from river Cauvery in India - Sibina Mol, S.; Jaiswar, A. K.; Panikkar, P.; Behera, B. K.; Sanath Kumar, H.; Roshith, C. M.; Vijaykumar, M. E.; Sharma, S. K.; Manna, R. K.; Das, B. K. (Indian Journal of Fisheries, 2019)
Length-weight relationship (LWR) of five species of the genus Labeo (Family: Cyprinidae) namely L. rohita (Hamilton,1822), L. calbasu (Hamilton,1822), L. bata (Hamilton,1822), L. dyocheilus (McClelland, 1839) and L. porcellus (Heckel, 1844), based on 214 specimens collected from Cauvery River in Peninsular India, were established. Sampling was carried out from December 2017 to December 2018 at around three months interval. The value of regression coefficient (b) ranged from 2.6147 (L. bata) to 3.2855 (L. dyocheilus). A new maximum length of 41 cm for L. porcellus has been recorded. For L. porcellus, LWR is established for the first time while for other species (except L. rohita); it is estimated for the first time from a peninsular river in India. Relative condition factor estimated for the five fish species did not show large scale variation (1.001 to 1.019). Keywords: Cauvery, Condition factor, Labeo, Length-weight relationship